Efficacy of Apamarga Pratisaraneeya Teekshna Kshara in the Management of Arsha (Internal Haemorrhoids): A Case Series - Koriya, Hetal; Beladar, Priti; Kumar, P Hemantha (Asian Journal of Biological and Life Sciences, 2026)
Introduction: Haemorrhoids are most common anorectal disorder causing mucosal prolapse, bleeding, discomfort and pain if associated with infection or thrombosis. Many conventional parasurgical and surgical procedures are performed nowadays for haemorrhoids and this may cause pain, delayed wound healing, post operative urine retention. In Ayurveda it is correlated with Arsha and advocates the use of Kshara in haemorrhoids due to its Chhedana(excision), Bhedana (incision) and Lekhana (scrapping) properties, which is minimal invasive day care procedure and cost-effective. This case series presents clinical outcomes of Apamarga Pratisaraneeya Teekshna Kshara (medicated alkali of Achyranthes aspera) in the management of Arsha. Material and Methods: three patients with complaints of bleeding, mass protrusion and pain were clinically and by proctoscopic examination diagnosed as second degree internal haemorrhoids and documented for the case series. All patients underwent for Kshara Karma under local anaesthesia. Patients were assessed for prolapse, bleeding, sphincter tone and pain post operatively at every week up to 4 weeks. Results: reduction in pile mass or normal anal cushions were seen in all patients in 3 weeks. Patients reported significant decrease in pain, bleeding and sphincter tone was also normal. No post operative complications or recurrence were observed in follow up period. Conclusion: Kshara Karma is effective, minimal invasive and day care procedure in the management of internal haemorrhoids.
Keywords: Arsha; Kshara Karma; Minimal Invasive